Assessment of Government Feeding Programme on Improved Nutritional Health Status of Secondary School Students in Maiduguri, Borno State - Tijjani, Sumayya Abdulkarim; Balami, Adamu; Abdulkadir, Kamar (Journal of Food Technology Research, 2017)
This study assessed government feeding programme on improved nutritional health status of secondary school students in Maiduguri, Borno state, Nigeria. Objectives and corresponding research questions were used in the study. The research design adopted for this study was survey research method. The target population for this study comprised of day public secondary schools in Maiduguri, Borno state, with a total population of nine thousand three hundred and thirty eight (9,338) students. Five public secondary schools were selected using purposive sampling technique. The sample of 934 students was selected using simple and stratified random sampling techniques. A self- developed questionnaire on government feeding programme among students in Maiduguri, Borno State was the instrument of data collection. The response mode for the instrument was a modified four(4) points Likert type scale with a response mode of strongly agree, agree, disagree and strongly disagree. Descriptive statistics of frequency counts, and percentage scores were used to answer the research question, while Chi-square was used to test the hypotheses at 0.05 level of significance. The results showed that the school feeding programme improved the nutritional health status of the students. Based on the findings of the study, it was recommended that Government should employ qualified food scientists, nutritionists, dieticians and caterers to assist in running the programme and to make them responsible for the purchase of needed food items to be cooked in schools. Furthermore, Government should also encourage more international donor agencies like the International Non-governmental organizations to come in with more improved varieties of school meals to increase the nutritional health status of the internally displaced students in the society. School feeding programmes should encompass both public and private primary and secondary educational institutions across the country. Feeding should be well guided by a menu which reflects the nutritional need for energy and micronutrients body requirements of the particular geographical area.